Hubungan Motivasi dan Dukungan Keluarga dalam Pengendalian Hipertensi dengan Tekanan Darah pada Pasien Hipertensi - Peronika, Feny; Efitra, Efitra; Rachmadanur, N. (Jurusan Keperawatan Mandiri Poltekkes Kemenkes Padang, 2024)
Hypertension is a non-communicable disease which is the main factor causing various diseases such as stroke, heart and kidney. Based on data from the Andalas Health Center, it was found that there were 203 hypertension patients in April 2023. A survey conducted on hypertensive patients aged 40-60 years found 4 people with uncontrolled blood pressure (> 140/80 mmHg) and 2 people with controlled blood pressure (≤140/80 mmHg), 4 people who still consume fatty foods regularly excessive daily and 2 respondents who have reduced consumption of fatty foods, 4 people who consume excessive sodium and 2 people who have reduced sodium consumption, 4 people who diligently eat vegetables 4-5 times a week and 2 people who rarely eat vegetables in a week , 5 people who have no desire to exercise in a week and 1 respondent who has a desire to exercise every week. Furthermore, 3 hypertensive patients who are always reminded by their families in controlling hypertension and 3 people who are rarely reminded to control their hypertension, such as taking regular medication and managing their diet. The research objective was to determine the relationship between motivation and family support in controlling hypertension and blood pressure in hypertensive patients in the Andalas sub-district, the Andalas Health Center in 2023. The research design was a cross-sectional study. The study was conducted from October 2022 to July 2023. The study population was all hypertension patients who were registered at the Andalas Health Center visit in the Andalas sub-district, consisting of 68 people. All populations are used as research subjects. Data collection was carried out by interviewing questionnaires and direct measurements. Univariate data analysis using descriptive statistics in the form of frequency and percentage distributions, bivariate analysis using the chi-square test.